A brittle‐2 transgene increases maize yield by acting in maternal tissues to increase seed number. (7th December 2017) - Hannah, L. Curtis; Shaw, Janine R.; Clancy, Maureen A.; Georgelis, Nikolaos; Boehlein, Susan K.
Abstract: The enzyme ADP‐glucose pyrophosphorylase is essential for starch biosynthesis and is highly regulated. Here, mutations that increased heat stability and interactions with allosteric effectors were incorporated into the small subunit of the isoform known to be expressed at high levels in the maize endosperm. The resulting variants were transformed into maize with expression targeted to the endosperm. Transgenes harboring the changes increased yield some 35%; however, yield enhancement occurred via an increase in seed number rather than by increased seed weight. Interestingly, seed number increase is controlled by the genotype of the plant rather than the genotype of the seed as seeds increase in number whether or not they contain the transgene as long as the maternal parent has the transgene. The transgene is however expressed in the endosperm, and the altered allosteric and stability properties initially seen in Escherichia coli expression experiments are also seen with the endosperm‐expressed gene. The extent of seed number increase is positively correlated with the average daily high temperature during the first 4 days postpollination. While these results were unexpected, they echo the phenotypic changes caused by the insertion of an altered large subunit of this enzyme reported previously ( Plant Cell, 24, 2012, 2352). These results call into question some of the reported fundamental differences separating starch synthesis in the endosperm vis‐à‐vis other plant tissues.